Neutrophil Elastase Inhibitor Following Liver Resection: A Matched Cohort Study - Yamazaki, Shintaro (Hepat Mon, 2015)
BACKGROUND: Sivelestat is a neutrophil elastase inhibitor (NEI) with positive impact on the respiratory complications in thoracic surgery. Based on the findings of a recent study, NEI may have a good response for avoiding ischemia reperfusion injury in liver resection. OBJECTIVES: The current study aimed to examine the impact of NEI on the postoperative outcomes after liver resection. PATIENTS AND METHODS: The data were collected from 374 consecutive patients scheduled to undergo liver resection. Seven perioperative variables were matched on the basis of the patients’ background. Then, the NEI (n = 61) and control (n = 61) groups were compared. NEI was administered at a dose of 0.2 mg/kg/h for three days from the postoperative day 0 (POD0). The liver function, coagulation activity, inflammatory response, respiratory complications, and overall complications were compared. RESULTS: The levels of serum interleukin-6 (NEI group: 113 pg/mL [26.9 - 522.0] vs. control group: 174 [28.6 - 1040.6], P < 0.01) and C-reactive protein (CRP) (2.9 IU/L [range: 0.1 - 8.6] vs. 4.11 [0.3 - 13.8], P = 0.01) on the first postoperative day (POD1) and the alveolar-arterial oxygen tension difference (32.3 Torr [-28.6 - 132.3] vs. 46.6 [-11.2 - 251.6], P = 0.04) on the third postoperative day (POD3) were significantly lower in the NEI group than the control group. The rate of pleural effusion was significantly lower in the NEI group compared to that of the control group [13 patients (21.3%) vs. 23 (37.7%), P = 0.04]. However, the coagulation activities (P = 0.68), liver function (P = 0.69), non-respiratory complications (P = 0.84), and overall complications (P = 0.71) did not differ significantly between the groups. CONCLUSIONS: Intravenous NEI administration had positive impact on the postoperative inflammatory response and oxygenation while it did not affect either coagulation or the liver function, as well as severe grade complications following resection.